2015
DOI: 10.1080/10871209.2015.1016387
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tolerance for Wildlife: Clarifying Relations Between Concepts and Measures

Abstract: Two parallel lines of inquiry, tolerance for and acceptance of wildlife populations, have arisen in the applied literature on wildlife conservation to assess probability of successfully establishing or increasing populations of controversial species. Neither of these lines is well grounded in social science theory, and diverse measures have been employed to assess tolerance, which inhibits comparability across studies. We empirically tested behavioral measures of tolerance against self-reports of previous poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 28 publications
(46 reference statements)
4
62
1
Order By: Relevance
“…The association between the two acceptance measures was weaker than in previous research (e.g., Bruskotter et al, 2015) and slightly different variables were confirmed predictors. For example, whereas emotions were more important predictors of attitudes, beliefs about ES food/hunting and EDS displayed stronger associations with acceptance capacity.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…The association between the two acceptance measures was weaker than in previous research (e.g., Bruskotter et al, 2015) and slightly different variables were confirmed predictors. For example, whereas emotions were more important predictors of attitudes, beliefs about ES food/hunting and EDS displayed stronger associations with acceptance capacity.…”
Section: Discussioncontrasting
confidence: 90%
“…The composite measures displayed good reliability (α = .91). Previous research of wildlife acceptance capacity has included measures reflecting whether people would prefer the wildlife population to decrease or increase and the potential for coexistence (Bruskotter et al, 2015;Skupien et al, 2016). In the present study, two questions relevant in the goose context were included: (a) "What is your perception of the goose population in your municipality?"…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent examples are human-wildlife interactions, where the success of any mitigation measures completely hinges on the cooperation of the people affected. In such cases, it is crucial to implement successful communication to improve public perception of conservation programs and to foster people's tolerance toward wildlife (Bruskotter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The food pyramid (c) illustrates that biomass reduces at higher trophic levels and is dependent on the amount of vegetation in desert landscapes supportive of management actions like lethal control for dealing with human-wildlife conflicts (Manfredo et al, 2016). Tolerance is an indicator of attitudes toward wildlife, defined more specifically as an individual's acceptance of negative effects and desire for positive effects that arise from interactions with wildlife (Bruskotter, Singh, Fulton, & Slagle, 2015). People who have high tolerance of a wildlife species prefer larger populations of that species.…”
Section: Carnivoresmentioning
confidence: 99%